Ocular cicatricial pemphigoid antigen: Partial sequence and biochemical characterization - Tyagi, Shivraj (The National Academy of Sciences of the USA, 1996)
Ocular cicatricial pemphigoid (OCP) is an autoimmune disease that affects mainly conjunctiva and other squamous epithelia. OCP is histologically characterized by a separation of the epithelium from underlying tissues within the basement membrane zone. Immunopathological studies demonstrate the deposition of anti-basement membrane zone autoantibodies in vivo. Purified IgG from sera of patients with active OCP identified a cDNA clone from a human keratinocyte cDNA library that had complete homology with the cytoplasmic domain of β4-integrin. The sera recognized a 205-kDa protein in human epidermal, human conjunctiva, and tumor cell lysates that was identified as β4-integrin by its reaction with polyclonal and monoclonal antibodies to human β4-integrin. Sera from patients with bullous pemphigoid, pemphigus vulgaris, and cicatricial pemphigoid-like diseases did not recognize the 205-kDa protein, indicating the specificity of the binding. These data strongly implicate a role for human β4-integrin in the pathogenesis of OCP. It should be emphasized that multiple antigens in the basement membrane zone of squamous epithelia may serve as targets for a wide spectrum of autoantibodies observed in vesiculobullous diseases. Molecular definition of these autoantigens will facilitate the classification and characterization of subsets of cicatricial pemphigoid and help distinguishing them from bullous pemphigoid. This study highlights the function and importance of β4-integrin in maintaining the attachment of epithelial cells to the basement membrane.